A Scientometric Analysis of 20 Years of Research on Breast Reconstruction Surgery: A Guide for Research Design and Journal Selection - Mehrdad Moghimi; Mehdi Fathi; Ali Marashi; Freshteh Kamani; Gholamreza Habibi; Armin Hirbod-Mobarakeh; Marjan Ghaemi; Mahdi Hosseinian-Sarajehlou (Archives of Plastic Surgery, 2013)
BackgroundBreast reconstruction refers to the rebuilding of a woman's breast using autologous tissue or prosthetic material to form a natural-looking breast. It is increasingly offered to women undergoing mastectomy for breast cancer. However, there is no systematic analysis available for the expanding area of research on breast reconstruction.MethodsA bibliometric method was used to obtain a view of the scientific production about breast reconstruction by data extracted from the Institute for Scientific Information (ISI). Specific parameters were retrieved from the ISI. Articles about breast reconstruction were analyzed to obtain a view of the topic's structure, history, and document relationships using HistCite software. Trends in the most influential publications and authors were analyzed.ResultsThe number of articles was constantly increasing. Most highly cited articles described the methods of flap construction in the surgery. Other highly cited articles discussed the psychological or emotional aspects of breast reconstruction, skin sparing mastectomy, and breast reconstruction in the irradiated breast.ConclusionsThis was the first breast reconstruction scientometric analysis, representing the characteristics of papers and the trends of scientific production. A constant increase in the number of breast reconstruction papers and also the increasing number of citations shows that there is an increasing interest in this area of medical science. It seems that most of the research in this field is focused on the technical aspects of surgery.